(untitled) (Revista Cientifica Ingenio Magno, 2023)
Abstract— AISI 1018 steel is used in the manufacture of machinery and in the mechanical construction of structures. Due to its good degree of machinability, it has been used in link axles, anchors for foundations, pins, screws, and tools for agriculture. In the present work, a 2k factorial design of experiments was developed and analyzed to evaluate the effect of cutting speed (200 and 150 [m/min]), feed (0.1 and 0.05 [mm/rev]) and cutting depth (1 and 0.5 [mm]). The root means square roughness in dry turning on an AISI 1018 steel bar was measured. A G-code was programmed to machine the tests on an EMCO CNC lathe, considering the combinations of the cutting parameters and the randomness of the experiment, the surface roughness was measured. Finally, a program was made in the MATLAB software to generally solve the 2k design of experiments and obtain the effects. Contour and surface plots are showed. The results obtained show that the only factor that significantly affects the roughness response is the feed. It was concluded that the less progress a better surface finish is obtained.